Assessment of Upper Extremity Venous Compliance in Patients With Abdominal Aortic Aneurysms. (November 2020) - Skoog, Johan; Shlimon, Kristian; Bjarnegård, Niclas; Lindenberger, Marcus
Abstract : Objective: Abdominal aortic aneurysm (AAA) is associated with morphological and functional changes in both aneurysmal and non-aneurysmal arteries. However, it remains uncertain whether similar changes also exist in the venous vasculature. The aim of this study was to evaluate global venous function in patients with AAA and controls. Methods: This experimental study comprised 31 men with AAA (mean ± standard deviation age 70.0 ± 2.8 years) and 29 male controls (aged 70.6 ± 3.4 years). Venous occlusion plethysmography (VOP) was used to evaluate arm venous compliance at venous pressures between 10 and 60 mmHg in steps of 5 mmHg. Compensatory mobilisation of venous capacitance blood (capacitance response) was measured with a volumetric technique during experimental hypovolaemia induced by lower body negative pressure (LBNP). Results: The VOP induced pressure–volume curve was significantly less steep in patients with AAA (interaction, p  < .001), indicating lower venous compliance. Accordingly, the corresponding pressure–compliance curves displayed reduced venous compliance at lower venous pressures in patients with AAA vs. controls (interaction, p  < .001; AAA vs. control, p  = .018). After adjusting for arterial hypertension, diabetes mellitus, hyperlipidaemia, chronic obstructive pulmonary disease, and smoking, VOP detected differences in venous compliance remained significant at low venous pressures, that is, at 10 mmHg ( p  = .008), 15 mmHg ( p  = .013), and 20 mmHg ( p  = .026). Mean venous compliance was negatively correlated with aortic diameter (r = −.332, p  = .010). Mobilisation of venous capacitance response during LBNP was reduced by approximately 25% in patients with AAA ( p  = .030), and the redistribution of venous blood during LBNP was negatively correlated with aortic diameter (r = −.417, p  = .007). Conclusion: Men with AAA demonstrated reduced venous compliance and, as a result, a lesser capacity to mobilise peripheral venous blood to the central circulation during hypovolaemic stress. These findings imply that the AAA disease may be accompanied by functional changes in the venous vascular wall.